BANK CONCENTRATION AND BANKING STABILITY: EVIDENCE FROM EAGLE GROUP - Hac, Le Dinh (Universitas Brawijaya, Indonesia, 2021)
The study was conducted to assess the impact of the banking sector's concentration on the banking system's stability in Emerging and growth-leading economies (EAGLEs).Â In addition, the study also analyzed the role of macroeconomic factors in bank stability. By applying Bayesian multivariate linear regression, the posterior probability results show that money supply growth and credit growth erode the soundness of the banking system. On the other hand, economic growth helps to improve banking stability, but this effect is not obvious; surprisingly, inflation also increases the banking stability of the Emerging and growth-leading economies. Finally, the study shows that the equity ratio to total assets has a reverse relationship with bank stability. Due to data limitations, this study has not yet examined the role of macroprudential policy instruments in maintaining banking stability. Hence, in future studies, besides the factors considered in this study, we should focus on analyzing the impact of macroprudential policy instruments on banking stability.